Spatio-temporal variability in the Brazil-Malvinas Confluence Zone (BMCZ), based on spectroradiometric MODIS-AQUA chlorophyll-a observations - Telesca, Luciano (2018)
The Brazil—Malvinas Confluence Zone (BMCZ) is characterized by high environmental variation, which could be reflected in several optical types of water, from one containing only phytoplankton and sea water to other optically more complex. In this paper, we analyze the spatio-temporal variability of the Chlorophyll-a detected by the ocean color sensor (CHLAsat) in BMCZ in order to understand its environmental variability. We use the MODIS-Aqua CHLAsat monthly composites imagery from 2002 to 2015, and applied two statistical methods: the correlogram-based robust periodogram to identify, over a broad spectrum of temporal, the most significant periodicities, and the pixel gradient distribution to study the spatial-temporal gradients within the BMCZ and variations over the continental shelf and coastal waters. Our results point out to the predominance of the annual cycle over most of the investigated area, although an area from latitude 378S in direction NE, alongshore of Uruguay to Brazil, evidences interannual periodicities, possibly related to variations in the discharge of the Rio de la Plata associated with the El Niño phenomena. The ocean color spectroradiometric signature in terms of pixel gradient presents a relatively high variability (0.0 to 0.65 mg m 3 ); in particular the high values of the pixel gradient correspond to saline front of the estuarine system of Rio de la Plata, and to the strip of the platform that extends along the isobaths of 80 m (coast of Uruguay), especially in the center and south of the study area.